Hygienic characteristic of the electromagnetic situation created by the electromagnetic radiation of the antennas of mobile base stations in Cherkasy region before and after the introduction of 4G technology - Halak , S.S.; Dumansky, V.Yu.; Nikitina, N.G.; Bitkin, S.V.; Bezverkha , A.P. (Medicni Perspektivi, 2021)
This work is part of our researches to study the distribution of electromagnetic radiation from mobile base stations in populated areas. The aim of this work was to study and analyze the electromagnetic situation before and after the introduction of fourth generation 4G technology at mobile base stations. We analyzed the maximum and average levels of electromagnetic radiation from mobile base stations located in Cherkasy region. The electromagnetic situation was studied both in urban areas and in rural areas. It was found that after the introduction of the fourth generation 4G technology at the mobile base stations, the levels of electromagnetic radiation in Cherkasy region increased significantly. The median of maximum levels of electromagnetic radiation increased by 155.6% (in particular, in urban areas by 194.1%), and the median of average levels - by 75.2% (in particular, in urban areas by 141.1%). No significant changes in electromagnetic radiation levels were detected before and after the modernization of mobile base stations in rural areas. It has been proven that there are no prerequisites for increasing the maximum permissible level to 100 μW/cm2 when implementing 4G and 5G technologies at mobile base stations.